Telework and Time Use in the United States - Sabrina Wulff Pabilonia; Victoria Vernon (Institute of Labor Economics (IZA), 2020)
Remote work is rapidly increasing in the United States. Using data on full-time wage and salary workers from the 2017–2018 American Time Use Survey Leave and Job Flexibilities Module, this paper examines the characteristics of teleworkers, the effects of teleworking on wages, and differences in time-use patterns between office and work-at-home workdays. We find that some teleworkers earn a wage premium, but it varies by occupation, gender, parental status, and teleworking intensity. Teleworkers also spend less time on commuting and grooming activities but more time on leisure and household production activities and more time with family on work-at-home days.
Keywords: J22; J31; D13; 330; working from home; telework; telecommuting; commuting; home-based work; alternative work arrangements; work-life balance; time use; wages